Pathotype surveillance and pre-emptive breeding against black and brown rusts of wheat in Nilgiri hills - V.K. VIKAS, P. NALLATHAMBI, UMA MAHESHWARI, R. NISHA; JOHN PETER, J. KUMAR*, M. SIVASAMY, P. JAYAPRAKASH (Indian Phytopathology, 2015)
Surveillance in Nilgiri hills was conducted from September 2010 to November 2012. There were dominance of pathotypes (pts) 77-5 (121R63-1), 77-7 (121R127) and 77-8 (253R31) of brown rust, and 40A (62G29) and 40-1(62G29-1) of black rust in Nilgiri hills. Majority of resistant genes in cultivars released for peninsular and central zones are susceptible to pts occurring in Nilgiri hills except Lr24 for brown rust and Sr31 for black rust. Black rust resistant gene, Sr31, confers immunity in India. It is susceptible to race Ug99, hence protection due to this gene is at risk due to identification of matching virulences in other countries. Cultivars in peninsular and central India need to be fortified with additional resistant genes for achieving longer protection against wheat rusts. Several useful resistant genetic stocks pyramided with number of rust resistant genes have been developed at IARI Regional Station, Wellington and can be utilised in breeding durable resistant wheat varieties. All these stocks have been listed and can be procured on demand.